Progressive Increase of Inflammatory CXCR4 and TNF-Alpha in the Dorsal Root Ganglia and Spinal Cord Maintains Peripheral and Central Sensitization to Diabetic Neuropathic Pain in Rats. (14th March 2019) - Zhu, Dan; Fan, Tingting; Huo, Xinyue; Cui, Jian; Cheung, Chi Wai; Xia, Zhengyuan
Abstract : Diabetic neuropathic pain (DNP) is a common and serious complication of diabetic patients. The pathogenesis of DNP is largely unclear. The proinflammation proteins, CXCR4, and TNF- α play critical roles in the development of pain, while their relative roles in the development of DNP and especially its progression is unknown. We proposed that establishment of diabetic pain models in rodents and evaluating the stability of behavioral tests are necessary approaches to better understand the mechanism of DNP. In this study, Von Frey and Hargreaves Apparatus was used to analyze the behavioral changes of mechanical allodynia and heat hyperalgesia in streptozotocin-induced diabetic rats at different phases of diabetes. Moreover, CXCR4 and TNF- α of spinal cord dorsal and dorsal root ganglia (DRG) were detected by western blotting and immunostaining over time. The values of paw withdrawal threshold (PWT) and paw withdrawal latencies (PWL) were reduced as early as 1 week in diabetic rats and persistently maintained at lower levels during the progression of diabetes as compared to control rats that were concomitant with significant increases of both CXCR4 and TNF- α protein expressions in the DRG at 2 weeks and 5 weeks (the end of the experiments) of diabetes. By contrast, CXCR4 and TNF- α in the spinal cord dorsal horn did not significantly increase at 2 weeks of diabetes while both were significantly upregulated at 5 weeks of diabetes. The results indicate that central sensitization of spinal cord dorsal may result from persistent peripheral sensitization and suggest a potential reference for further treatment of DNP.